Synthesis of Some Substituted Indane-Amino Acid Derivatives - Gommaa, A.M.; El-Gazzar, M.A.; Badie, M.F.; Ahmed, F.S.; Radi, A.H.M. (Asian Journal of Chemistry, 2010)
Synthesis and antimicrobial evaluation of some new 3-keto-4.7-dimethylindane-1-carbonylamino acid methyl esters (III–VIII), 3-keto·4.5-benzoindane-1-carbonylamino acid methyl esters (IX–XII) and the corresponding hydrazides and some dipeptide methyl ester derivatives (XIII–XXXII) are described.